2022
DOI: 10.3389/fphys.2021.794641
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exercise-Induced Molecular Processes and Vitamin D in Improving Cardiorespiratory Fitness and Cardiac Rehabilitation in Patients With Heart Failure

Abstract: Heart failure (HF) still affects millions of people worldwide despite great advances in therapeutic approaches in the cardiovascular field. Remarkably, unlike pathological hypertrophy, exercise leads to beneficial cardiac hypertrophy characterized by normal or enhanced contractile function. Exercise-based cardiac rehabilitation improves cardiorespiratory fitness and, as a consequence, ameliorates the quality of life of patients with HF. Particularly, multiple studies demonstrated the improvement in left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…At the beginning of the pandemic, epidemiologic studies showed that individuals of advanced age, male gender, and with preexisting illnesses such as cancer or cardiovascular diseases (CVD), metabolic disorders, diabetes, and obesity, were at higher risk of developing complications and severe forms of COVID-19, and were associated with unfavorable outcomes [5] . CVD is one of the leading causes of mortality in the world, whose prevalence is growing due to the aging population and the increase in age-related diseases such as diabetes mellitus, obesity, dyslipidemia, and hypertension, which are risk factors for heart disease [6] . In addition, poor life choices such as inadequate diet and sedentary lifestyle coupled with stress contribute to an even greater number of CVD cases [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the pandemic, epidemiologic studies showed that individuals of advanced age, male gender, and with preexisting illnesses such as cancer or cardiovascular diseases (CVD), metabolic disorders, diabetes, and obesity, were at higher risk of developing complications and severe forms of COVID-19, and were associated with unfavorable outcomes [5] . CVD is one of the leading causes of mortality in the world, whose prevalence is growing due to the aging population and the increase in age-related diseases such as diabetes mellitus, obesity, dyslipidemia, and hypertension, which are risk factors for heart disease [6] . In addition, poor life choices such as inadequate diet and sedentary lifestyle coupled with stress contribute to an even greater number of CVD cases [6] .…”
Section: Introductionmentioning
confidence: 99%
“…CVD is one of the leading causes of mortality in the world, whose prevalence is growing due to the aging population and the increase in age-related diseases such as diabetes mellitus, obesity, dyslipidemia, and hypertension, which are risk factors for heart disease [6] . In addition, poor life choices such as inadequate diet and sedentary lifestyle coupled with stress contribute to an even greater number of CVD cases [6] . The reason why patients with CVD are generally prone to develop severe forms of infective disorders lies in the already present impaired endothelial function and activity, deteriorated immune response and platelet hyperreactivity [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…However, during this rigorous evaluation, it became evident that certain articles needed to be excluded for specific reasons. For example, 1 article focused primarily on the human heart rather than skeletal muscle (15), which did not align with the objectives of the present study. Additionally, several articles did not directly address the topic of hypertrophy (18,19,29).…”
Section: Resultsmentioning
confidence: 86%